Pengaruh Literasi Keuangan Terhadap Kemampuan Mengelola Keuangan Mahasiswa Penerima Beasiswa KIP Prodi Pendidikan Ekonomi Universitas Nusa Cendana - Anggi Apriayani Manafe; Yeheskial Nggandung; Ari Data (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of financial literacy on the financial management skills of students receiving the Indonesia Smart Card (KIP) scholarship in the Economics Education Study Program, Faculty of Teacher Training and Education, Nusa Cendana University. This study used a quantitative approach with an associative causal approach. The sample consisted of 160 students selected using a purposive sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS. The results indicate that financial literacy, consisting of financial knowledge, financial attitudes, and financial behavior, influences students' financial management skills. Both partially and simultaneously, these variables contribute to improving students' ability to plan, organize, and control their finances. These findings emphasize the importance of improving financial literacy among students to enable them to manage their finances wisely, effectively, and responsibly. Therefore, this research is expected to serve as a basis for developing financial education programs to support students' academic success and future financial well-being.